2022
DOI: 10.1109/tpwrd.2022.3145880
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Design of Ester-Filled Power Transformers: AC Stress Analysis

Abstract: In the last 20 years the use of ester fluids as an alternative to mineral oil for transformer insulation has been an active field of research and development. These liquids have a much lower environmental impact than mineral oils, besides reducing the transformer's fire risk. Although the use of natural and synthetic esters is nowadays frequent for certain applications, as for distribution transformers in highly populated areas, railway transformers or off-shore windmill transformers, the experience on large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Finally, the dielectric permittivity is important in the dielectric design of transformers, as the relationship between the permittivity of the fluid and paper will largely determine the distribution of the electric field throughout the insulating system [68]. This determines the electrical stress the materials withstand and the occurrence of partial discharges.…”
Section: Dielectric Permittivitymentioning
confidence: 99%
“…Finally, the dielectric permittivity is important in the dielectric design of transformers, as the relationship between the permittivity of the fluid and paper will largely determine the distribution of the electric field throughout the insulating system [68]. This determines the electrical stress the materials withstand and the occurrence of partial discharges.…”
Section: Dielectric Permittivitymentioning
confidence: 99%
“…Numerical simulations carried out have shown that the temperatures reached in a transformer using esters could be similar, or even lower, to those reached with mineral oils in adapted winding designs [12], [13], [14] Some manufacturers apply special treatments to improve the viscosity or the oxidation stability of these alternative liquids [15]. The effect of the fluid used on the degradation of the solid insulation, measured by the control of the chemical [16], mechanical [17] or light techniques [18] after a thermal [19] or electrical [20] ageing process, have also been afforded.…”
Section: Introductionmentioning
confidence: 95%
“…Another of its functions is to minimise the contact of cellulose and other materials with oxygen to reduce the risk of oxidation. For the liquid part of insulation, mineral oils have been the most widely used for over a century 1 . However, the controversy over the negative impact of mineral oils on the environment is nowadays a hot topic taken very seriously by environmentalists 2 .…”
Section: Introductionmentioning
confidence: 99%